Comment and response to the commentary: Related to ‘Follow-up study of the treatment outcomes at a psychiatric trauma clinic for refugees’ and ‘Cognitive behavioral psycho-therapeutic treatment at a psychiatric trauma clinic for Refugees: description and evaluation’ by Buhman et al. (Volume 25, No 1, 2015) - Harlacher, Uwe; Polatin, Peter; Buhmann, Caecilie Boeck; Nordentoft, Merete; Ekstroem, Morten; Lohmann, Jessica Carlsson; Mortensen, Erik Lykke (Torture Journal, 2018)
Comment and response to the commentary based on the two: ‘Follow-up study of the treatment outcomes at a psychiatric trauma clinic for refugees’ and ‘Cognitive-behavioral psycho-therapeutic treatment at a psychiatric trauma clinic for Refugees: description and evaluation’ by Buhman et al. (Volume 25, No 1, 2015)